2022
DOI: 10.3390/ma15186185
|View full text |Cite
|
Sign up to set email alerts
|

Study on Rheological Properties of Graphene Oxide/Rubber Crowd Composite-Modified Asphalt

Abstract: In order to improve the durability of asphalt pavement and prolong the service life of heavy traffic asphalt pavement, graphene oxide (GO) and rubber powder (RP) were used as composite modifiers to modify matrix asphalt. The high-temperature rheological properties of composite-modified asphalt at different temperatures and frequencies were analyzed. The influence of different stress levels on the viscoelastic properties of composite-modified asphalt was evaluated. The low-temperature rheological properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…During this process, sludge tended to be less viscous, demonstrating shearthinning (pseudoplastic) behavior. Similar rheological behaviors have been reported for sewage sludge [9], ink [27], foam [27], clay [29], paint [30] and chocolate [30], among others [30,31].…”
Section: Dwts Rheological Characteristicssupporting
confidence: 81%
See 1 more Smart Citation
“…During this process, sludge tended to be less viscous, demonstrating shearthinning (pseudoplastic) behavior. Similar rheological behaviors have been reported for sewage sludge [9], ink [27], foam [27], clay [29], paint [30] and chocolate [30], among others [30,31].…”
Section: Dwts Rheological Characteristicssupporting
confidence: 81%
“…During this process, sludge tended to be less viscous, demonstrating shearthinning (pseudoplastic) behavior. Similar rheological behaviors have been reported for sewage sludge [9], ink [27], foam [27], clay [29], paint [30] and chocolate [30], among others [30,31]. The apparent viscosity of DWTS at the beginning of the test (lowest shears rates) dropped dramatically, and then tended to a relatively constant value (highest shears rates) (Figure 5b).…”
Section: Dwts Rheological Characteristicssupporting
confidence: 81%
“…As can be seen from figure 2 (c), the slope of the damage curve when SBS modified asphalt is involved is significantly lower than that when the first two groups of matrix asphalt is involved, which further indicates that the stress sensitivity of the matrix asphalt is stronger, and the value of the damage factor is not completely near zero after the amplitude test. [7] It indicates that the strain range of the LAS test involving SBS modified asphalt needs to be expanded. In the figure, the effect of NRA and NRB on the damage curve is almost the same with staggered phenomenon, and the effect of PR and BR is second only to NRA and NRB.…”
Section: Fatigue Damage Curvementioning
confidence: 99%
“…To further enhance the performance of rubber-modified asphalt, researchers have made significant efforts. For instance, De Albornoz [14] and Qian [15] investigated the synergistic Materials 2023, 16, 7359 2 of 19 effects of CR and SBS and showed that the aging and mechanical performance of asphalt mixtures produced with rubber-modified asphalt was very similar to that of asphalt mixtures based on traditional SBS-modified asphalt. Li [16] found that oxidized graphene and rubber powder, as composite materials, improved the rheological properties of asphalt at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, De Albornoz [14] and Qian [15] investigated the synergistic Materials 2023, 16, 7359 2 of 19 effects of CR and SBS and showed that the aging and mechanical performance of asphalt mixtures produced with rubber-modified asphalt was very similar to that of asphalt mixtures based on traditional SBS-modified asphalt. Li [16] found that oxidized graphene and rubber powder, as composite materials, improved the rheological properties of asphalt at low temperatures. In addition, with reduced rubber particle size, rubber-modified asphalt has been proven to exhibit better low-temperature performance, elasticity, and adhesion [17,18].…”
Section: Introductionmentioning
confidence: 99%